THE RISE OF E-GOVERNANCE FOR RURAL COMMUNITIES WITH DIGITAL INDIA - Nahak, Duryodhan (ShodhKosh: Journal of Visual and Performing Arts, 2023)
India stands as the world’s largest young democracy and hosts the third-largest online community, following China and the United States. Yet, with the majority of its population living in rural areas, India faces challenges in competing with countries that boast stronger infrastructure, a more informed citizenry, and higher education levels. The global internet revolution, however, has created new opportunities for all nations to harness Information and Communication Technologies (ICTs) for efficient governance. Nearly every country, from the least developed to the most advanced, now maintains some form of e-governance presence. In this context, Digital India has emerged as a transformative initiative, aiming to bridge the gap and advance e-governance across rural communities. From enhancing agricultural productivity to improving healthcare access and ensuring transparency in financial transactions, these initiatives are set to elevate living conditions for millions. As India’s digital connectivity expands, ICTs, combined with the government’s drive toward digitization, will usher in a new era of e-governance, fundamentally changing how public services reach Indian citizens. This research paper follows the journey of Digital India as technology evolves, emphasizing its impact on rural technology adoption and the growth of e-governance services nationwide.